55.1k views
5 votes
Solve 36x^2+23=60x using quadratic formula


User Zilongqiu
by
4.8k points

1 Answer

6 votes

Answer:

x₁ = 0.6

x₂ = 1.07

Explanation:

36x² + 23 = 60x

36x² - 60x + 23 = 0

x = {-(-60)±√((-60²)-(4*36*23))} / (2*36)

x = {60±√(3600-3312)} / 72

x = {60±√288) / 72

x = {60±16.97) / 72

x₁ = {60-16.97} / 72 = 43.03/72 = 0.6 aprox.

x₂ = {60+16.97} / 72 = 76.97/72 = 1.07 aprox.

verify:

x₁

36*0.6² + 23 = 60*0.6

36*0.36 + 23 = 36

13 + 23 = 36

x₂

36*1.07² + 23 = 60*1.07

36*1.145 + 23 = 64.2

41.2 + 23 = 64.2

User Micah
by
5.1k points